2014
DOI: 10.3389/fnbeh.2014.00304
|View full text |Cite
|
Sign up to set email alerts
|

N-methyl-D-aspartate receptor-mediated glutamate transmission in nucleus accumbens plays a more important role than that in dorsal striatum in cognitive flexibility

Abstract: Cognitive flexibility is a critical ability for adapting to an ever-changing environment in humans and animals. Deficits in cognitive flexibility are observed in most schizophrenia patients. Previous studies reported that the medial prefrontal cortex-to-ventral striatum and orbital frontal cortex-to-dorsal striatum circuits play important roles in extra- and intra-dimensional strategy switching, respectively. However, the precise function of striatal subregions in flexible behaviors is still unclear. N-methyl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…After an initial learning phase, rats are tested repeatedly on the same set of rules that are alternated within and between sessions, and therefore they have to choose among strategies that they have already learned. In this respect, the procedure is different from other set‐shifting procedures in which flexibility is measured in a single session or two (Haluk & Floresco ; Dalton et al ; Ding et al ). It is possible that these procedures measure different aspects of behavioral flexibility; the former (Darrah et al and present work) models perseverative behavior and strategy selection and the latter (Haluk & Floresco ; Dalton et al ; Ding et al ) models the ability to rapidly adapt to new contingencies and to implement a novel behavioral strategy.…”
Section: Discussionmentioning
confidence: 99%
“…After an initial learning phase, rats are tested repeatedly on the same set of rules that are alternated within and between sessions, and therefore they have to choose among strategies that they have already learned. In this respect, the procedure is different from other set‐shifting procedures in which flexibility is measured in a single session or two (Haluk & Floresco ; Dalton et al ; Ding et al ). It is possible that these procedures measure different aspects of behavioral flexibility; the former (Darrah et al and present work) models perseverative behavior and strategy selection and the latter (Haluk & Floresco ; Dalton et al ; Ding et al ) models the ability to rapidly adapt to new contingencies and to implement a novel behavioral strategy.…”
Section: Discussionmentioning
confidence: 99%
“…3) Dopamine-glutamate interactions in the ventral striatum may be more important to maintaining higher forms of cognitive flexibility as opposed to the dorsal striatum. In this context, a recent study showed that infusions of AP5, a NMDA receptor antagonist, into the ventral striatum impaired strategy shifting (Ding et al 2014). A similar observation was reported by Haluk and Floresco (2009) when a D1 receptor antagonist was infused into the nucleus accumbens of rats.…”
Section: Discussionmentioning
confidence: 99%
“…Ragozzino and colleagues found that these deficits were accompanied by decreases in acetylcholine efflux (Palencia and Ragozzino, 2006) and could be mimicked by blocking muscarinic M1 (via pirenzepine) or stimulating M2 (via oxotremorine sesquifumurate), but not by antagonizing nicotinic (via mecamylamine), acetylcholine receptors in the DMS (Tzavos et al, 2004, McCool et al, 2008, Ragozzino et al, 2009). Somewhat surprisingly, given this evidence of a key role for DMS NMDARs in reversal, a recent study found no effect of DMS NMDAR antagonism (via AP5) on a visual-cue reversal learning task that was impaired by NMDAR blockade in the NAc (Ding et al, 2014). It may be that differences in the way reversal was tested across these studies accounts for this discrepancy, but further investigation would be needed to draw any firm conclusions.…”
Section: Neurochemical Modulation Of Reversalmentioning
confidence: 99%